Determination of central venous catheter complications: Internal jugular vein versus femoral vein catheterization (Annals of Medical Research, 2023)
Aim: This research aimed to compare the mechanical, thrombotic, and infectious complication ratio of the internal jugular vein with those of femoral vein catheterization.Materials and Methods: It is a single-center retrospective study. One hundred seventy-nine pediatric patients undergoing central venous catheter insertion in the intensive care unit were selected from February 2020 to August 2021. The patients were divided into 2 groups based on catheter type; internal jugular versus femoral venous catheterization. Procedure complications rates were assessed. However, jugular catheterization was performed under ultrasound guidance, and femoral venous catheterization was inserted via an original landmark-based technique. Thromboprophylaxis was performed on all patients without coagulopathy.Results: The overall rate of procedural complications was 20%. The subcutaneous hematoma was the most common mechanical complication and higher in femoral attempts (p= 0.001), followed by arterial injury (p= 0.002). Thrombotic complications were similar between the two groups (p= 0.053). Infections complications were higher in femoral venous catheterization (p= 0.016).Conclusion: Femoral venous catheterization is associated with a greater risk of mechanical and infectious complications than internal jugular venous catheterization. Usage of ultrasound during catheterization procedures decreases mechanical complications.
Keywords: Central catheterization; Internal jugular veins; Femoral veins; Complication